Low Complexity of Infection Is Associated With Molecular Persistence of Plasmodium falciparum in Kenya and Tanzania - Topazian, Hillary M.; Moser, Kara A.; Ngasala, Billy; Oluoch, Peter O.; Forconi, Catherine S.; Mhamilawa, Lwidiko E.; Aydemir, Ozkan; Kharabora, Oksana; Deutsch-Feldman, Molly; Read, Andrew F.; Denton, Madeline; Lorenzo, Antonio; et al. (Frontiers in Epidemiology, 2022)
Background: Plasmodium falciparum resistance to artemisinin-based combination therapies (ACTs) is a threat to malaria elimination. ACT-resistance in Asia raises concerns for emergence of resistance in Africa. While most data show high efficacy of ACT regimens in Africa, there have been reports describing declining efficacy, as measured by both clinical failure and prolonged parasite clearance times. Methods: Three hundred children aged 2-10 years with uncomplicated P. falciparum infection were enrolled in Kenya and Tanzania after receiving treatment with artemether-lumefantrine. Blood samples were taken at 0, 24, 48, and 72 hours, and weekly thereafter until 28 days post-treatment. Parasite and host genetics were assessed, as well as clinical, behavioral, and environmental characteristics, and host anti-malarial serologic response. Results: While there was a broad range of clearance rates at both sites, 85% and 96% of Kenyan and Tanzanian samples, respectively, were qPCR-positive but microscopy-negative at 72 hours post-treatment. A greater complexity of infection (COI) was negatively associated with qPCR-detectable parasitemia at 72 hours (OR: 0.70, 95% CI: 0.53-0.94), and a greater baseline parasitemia was marginally associated with qPCR-detectable parasitemia (1,000 parasites/uL change, OR: 1.02, 95% CI: 1.01-1.03). Demographic, serological, and host genotyping characteristics showed no association with qPCR-detectable parasitemia at 72 hours. Parasite haplotype-specific clearance slopes were grouped around the mean with no association detected between specific haplotypes and slower clearance rates. Conclusions: Identifying risk factors for slow clearing P. falciparum infections, such as COI, are essential for ongoing surveillance of ACT treatment failure in Kenya, Tanzania, and more broadly in sub-Saharan Africa.